Acute Seizures—Work-Up and Management in Children - Romantseva, Lubov; Lin, Nan (Seminars in Neurology, 2020)
Seizures are common in the pediatric population; however, most children do not go on to develop epilepsy later in life. Selecting appropriate diagnostic modalities to determine an accurate diagnosis and appropriate treatment as well as with counseling families regarding the etiology and prognosis of seizures, is essential. This article will review updated definitions of seizures, including provoked versus unprovoked, as well as the International League Against Epilepsy operational definition of epilepsy. A variety of specific acute symptomatic seizures requiring special consideration are discussed, along with neonatal seizures and seizure mimics, which are common in pediatric populations.
Keywords: acute symptomatic seizures; febrile seizures; neonatal seizures; PNES; seizure mimics